Empowering Communities: Unleashing the Potential of Gunung Tunak Natural Park through Active Participation in Sustainable Tourism - Lale Salsya Noviyanti; Murianto; Uwi Martayadi (Advances in Tourism Studies, 2023)
This study aims to find the potential and participation of the community in developing the Gunung Tunak Nature Tourism Park destination. This type of research includes qualitative research. Data collection techniques through observation, interviews and documentation. The findings in this study indicate that the potential of Gunung Tunak Natural Tourism Park is in the form of potential natural resources in the form of diversity of flora and fauna as well as support for marine tourism objects in the forest circumference of Mount Tunak. The existing potential as a grant is in the form of hotels, restaurants, meeting rooms, camping areas, various types of captivity and management personnel who have received direct training by the Korean government through internships in ecotourism in South Korea. Increasing domestic and foreign tourist visits through Mertak Village as a tourist village, holding events at the Gunung Tunak Natural Tourism Park destination and the role of the community in maintaining and developing flora and fauna at Gunung Tunak Natural Park.